Short-term intravenous zoledronic acid in severe osteogenesis imperfecta : A report of three siblings of children (Faculty of Medicine Universitas Indonesia, 2008)
This report documented the clinical and biochemical side effects on the first dose of intravenous zoledronic acid therapy in three siblings with severe osteogenesis imperfecta. Zoledronic acid was administered in 50 ml 0.9% saline solution over a period of 30 minutes. All patients had fever during the first 6 to 48 hours after the first infusion. There were no renal side effects, apart from asymptomatic hypocalcemia and hypophosphatemia at 48 and 72 hours after zoledronic acid infusion. The minimal clinical side effects were easily manageable. (Med J Indones 2008; 17: 127-30)